Accounting and cash flow variables as determinants of stock returns : a predictive model - Boon, Kian Khoon (2008)
This paper re-examines Ou and Penman (1989a)'s conclusion that an extensive analysis of financial statements identifies one-year ahead earnings changes, with the inclusion of 18 additional cash flow descriptors.